2016
DOI: 10.1093/ndt/gfw335
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life across all stages of autosomal dominant polycystic kidney disease

Abstract: BackgroundA limited number of studies have assessed health-related quality of life (HRQoL) in autosomal dominant polycystic kidney disease (ADPKD). Results to date have been conflicting and studies have generally focused on patients with later stages of the disease. This study aimed to assess HRQoL in ADPKD across all stages of the disease, from patients with early chronic kidney disease (CKD) to patients with end-stage renal disease.MethodsA study involving cross-sectional patient-reported outcomes and retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
4
21
0
Order By: Relevance
“…Similar findings were found in the studies conducted by Pagel M et al, Eriksson E et al, reported that the QoL was impaired in stage 5D compared to other stages (p -0.000). 10,11 Eriksson E et al, also reported the better EQ-5D index and VAS scores for the CKD stages 3-5 and 5D than the present study. 11 Whereas in a study conducted by Kathib ST et al, reported comparatively less EQ-5D index and VAS scores and Sakthong P et al, reported the better EQ-5D index and VAS scores for the CKD-5D than present study.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Similar findings were found in the studies conducted by Pagel M et al, Eriksson E et al, reported that the QoL was impaired in stage 5D compared to other stages (p -0.000). 10,11 Eriksson E et al, also reported the better EQ-5D index and VAS scores for the CKD stages 3-5 and 5D than the present study. 11 Whereas in a study conducted by Kathib ST et al, reported comparatively less EQ-5D index and VAS scores and Sakthong P et al, reported the better EQ-5D index and VAS scores for the CKD-5D than present study.…”
Section: Resultssupporting
confidence: 61%
“…10,11 Eriksson E et al, also reported the better EQ-5D index and VAS scores for the CKD stages 3-5 and 5D than the present study. 11 Whereas in a study conducted by Kathib ST et al, reported comparatively less EQ-5D index and VAS scores and Sakthong P et al, reported the better EQ-5D index and VAS scores for the CKD-5D than present study. 12,13 In the study, the most commonly affected domains among the study population were usual activities (79%), pain (76.20%) and anxiety and depression (71.91%).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Eriksson and colleagues (2017) present a study assessing HRQL across all stages of autosomal dominant polycystic kidney disease (ADPKD): chronic kidney disease, dialysis, and transplant. PCS scores for these patients ranged from 34.9 for dialysis patients to 51.2 for early chronic kidney disease patients [ 38 ]. MCS scores ranged from 47.0 for dialysis patients to 52.7 for kidney transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…stages 4–5) and available data are derived from monocentric, cross-sectional studies conducted prior to the availability of tolvaptan [ 2 ]. A small number of studies have investigated QoL in early-stage ADPKD (CKD stages 1–3) finding that, while QoL is higher in early stages of the diseases than during the later stages, early-stage ADPKD has significant physical and emotional impact on patients [ 15 , 16 ]. However, these studies used generic measures of HRQoL, rather than questionnaires specifically designed to assess the disease-specific effects ADPKD has on patients’ HRQoL.…”
Section: Introductionmentioning
confidence: 99%